Disaster victim identification by kinship analysis: the Lampedusa October 3rd, 2013 shipwreck. (January 2020) - Bertoglio, Barbara; Grignani, Pierangela; Di Simone, Paola; Polizzi, Nicolò; De Angelis, Danilo; Cattaneo, Cristina; Iadicicco, Agata; Fattorini, Paolo; Presciuttini, Silvano; Previderè, Carlo
Highlights: A boat full of more than 500 migrants sank in the Mediterranean in 2013. Genetic profiles were extracted both from victims and putative living relatives. The Identity by State (IBS) and the Identity by Descent (IBD) statistics were calculated. Genetic identifications were confirmed by pedigree analysis using FAMILIAS3. Abstract: On October 3rd, 2013 a boat carrying more than 500 migrants coming mostly from the Horn of Africa (Eritrea, Somalia, Ethiopia) sank near Lampedusa, a small Italian Island in the middle of the Mediterranean Sea. The recovered bodies were examined by a forensic team, and post mortem data (anthropological and odontological records, and DNA) were collected for identification. Genetic profiles based on 16 autosomal STRs were acquired from both victims and putative relatives recruited following an international call. The final genetic database included 363 victims and 43 reference persons from 36 independent families recruited until mid-2017, who were missing 35 first-degree and 6 second-degree relatives. A pairwise blind search approach was used to identify familial relationships within the victims and between victims and putative relatives. Two statistics were calculated, the Identity by State (IBS) and the Identity by Descent (IBD), the latter by using the DVI module of the FAMILIAS3 software to compute LRs and posterior probabilities. The putative identifications were confirmed in pedigree analysis using the information provided by the relatives. In selected cases, additional autosomal and lineage (Y-chromosome and mtDNA) markers were typed. Some critical points were highlighted: the lack for accurate allele and haplotype frequencies in African populations, especially for the lineage markers, and the need for a shared approach to the biostatistical interpretation of the results in DVI. In the end, 29 first-degree (parent-child and full sibs) out of 35 missing (83%), and 3 out of 6 of second-degree relatives (50%) showed a high statistical confidence for a positive identification. This study represents the first attempt to systematically deal with the genetic identification of African migrants who died in the Mediterranean Sea. The methodological and statistical approach used in this study was proved to be reliable and appropriate for future genetic identifications in other similar mass disasters.